Download presentation
Presentation is loading. Please wait.
Published byAshlynn Higgins Modified over 9 years ago
2
Multiply: a) x(x + 7) b) 6x(x 2 4x + 5) Solution a) x(x + 7) = x x + x 7 = x 2 + 7x b) 6x(x 2 4x + 5) = (6x)(x 2 ) (6x)(4x) + (6x)(5) = 6x 3 24x 2 + 30x Example
4
Multiply: (x + 4)(x 2 + 3). Solution F O I L (x + 4)(x 2 + 3) = x 3 + 3x + 4x 2 + 12 = x 3 + 4x 2 + 3x + 12 Example O I F L The terms are rearranged in descending order for the final answer. Multiply. a) (x + 8)(x + 5)b) (y + 4) (y 3) c) (5t 3 + 4t)(2t 2 1)d) (4 3x)(8 5x 3 ) Solution a) (x + 8)(x + 5)= x 2 + 5x + 8x + 40 = x 2 + 13x + 40 b) (y + 4) (y 3)= y 2 3y + 4y 12 = y 2 + y 12 Example
5
Solution c) (5t 3 + 4t)(2t 2 1) = 10t 5 5t 3 + 8t 3 4t = 10t 5 + 3t 3 4t d) (4 3x)(8 5x 3 ) = 32 20x 3 24x + 15x 4 = 32 24x 20x 3 + 15x 4 Example continued In general, if the original binomials are written in ascending order, the answer is also written that way.
6
Multiply. a) (x + 8) 2 b) (y 7) 2 c) (4x 3x 5 ) 2 Solution a) (x + 8) 2 = x 2 + 2 x 8 + 8 2 = x 2 + 16x + 64 Example
7
Example continued Solution (A – B) 2 = A 2 2AB + B 2 b) (y 7) 2 = y 2 2 y 7 + 7 2 = y 2 14y + 49 c) (4x 3x 5 ) 2 = (4x) 2 2 4x 3x 5 + (3x 5 ) 2 = 16x 2 24x 6 + 9x 10
8
Multiply. a) (x + 8)(x 8) b) (6 + 5w) (6 5w)c) (4t 3 3)(4t 3 + 3) Solution a) (x + 8)(x 8) = x 2 8 2 = x 2 64 b) (6 + 5w) (6 5w) = 6 2 (5w) 2 = 36 25w 2 c) (4t 3 3)(4t 3 + 3) = (4t 3 ) 2 3 2 = 16t 6 9
9
Function Notation Given f(x) = x 2 – 6x + 7, find and simplify each of the following. a) f(a) + 3b) f(a + 3) Solution a) To find f(a) + 3, we replace x with a to find f(a). Then we add 3 to the result. f(a) + 3 = a 2 – 6a + 7 + 3 = a 2 – 6a + 10 Examples b) To find f(a + 3), we replace x with a + 3 f(a + 3) = (a + 3) 2 – 6(a + 3) + 7 = a 2 + 6a + 9 – 6a – 18 + 7 = a 2 – 2
10
Examples
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.